2007
DOI: 10.1097/jsm.0b013e3180326836
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Plasma Volume and Serum Sodium Concentration Despite Body Weight Loss in Ironman Triathletes

Abstract: Plasma volume and serum [Na] were maintained in male Ironman triathletes, despite significant (5%) body weight loss during the course of the race. Body weight was not an accurate "absolute" surrogate of fluid balance homeostasis during prolonged endurance exercise. Clinicians should be warned against viewing these three regulatory parameters as interchangeable during an Ironman triathlon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 47 publications
(68 reference statements)
4
39
0
Order By: Relevance
“…In another study on 181 male Ironman triathletes, plasma volume and serum [Na + ] were maintained despite a significant body mass loss of 5% (Hew-Butler, et al, 2007). These authors concluded that body mass was not an accurate 'absolute' surrogate of fluid balance homeostasis during prolonged endurance exercise.…”
Section: Discussionmentioning
confidence: 89%
“…In another study on 181 male Ironman triathletes, plasma volume and serum [Na + ] were maintained despite a significant body mass loss of 5% (Hew-Butler, et al, 2007). These authors concluded that body mass was not an accurate 'absolute' surrogate of fluid balance homeostasis during prolonged endurance exercise.…”
Section: Discussionmentioning
confidence: 89%
“…2 In single Ironman triathlons, exercise-associated hyponatremia (EAH) is considered a frequent and serious problem. 3,4 EAH is defined as a decrease in plasma [Na + ] concentration < 135 mmol/l 5 and fluid overload is the likely aetiology. 4,6 However, regarding recent findings,…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that body mass change may not accurately represent the net effective body water change during prolonged exercise. However, this matter is hotly debated today, because some researchers have reported a difference between body mass change and net effective body water change (Hew-Butler et al, 2007;Nolte, Noakes, & Van Vuuren, 2011;Tam et al, 2011), whereas other investigators have reported no difference (Baker, Lang, & Kenney, 2009). Thus, the present field investigation determined if (a) body mass change was equivalent to effective body water change during ultra-endurance exercise and (b) the changes of body mass change and effective body water would be similar in three cyclist groups, with different exercise durations and ground speeds.…”
Section: Discussionmentioning
confidence: 96%
“…First, is water bound to glycogen and released only when glycogen is metabolised, or is this water freely available within the intracellular space at all times? This question is still debated today , with some authors claiming that water is bound to glycogen (Hew-Butler et al, 2007;King et al, 2008;Pastene, Germain, Allevard, Gharib, & Lacour, 1996;Rogers et al, 1997;Tam et al, 2011; and others proposing that this intracellular water is freely available as part of the total body water pool and not part of intracellular water gain (Baker et al, 2009;Cheuvront & Haymes, 2001;King et al, 2008). Second, if water is chemically bound to glycogen, what is the mass ratio of glycogen to water?…”
Section: Water Associated With Glycogenmentioning
confidence: 98%